Peningkatan Kapasitas Pemandu Wisata Melalui Pelatihan Basic Life Support dan P3K di Destinasi Wisata Alam Sendang Seruni, Banyuwangi - Dheanita Sekarini Octanisa; Reni Nur Jannah; Khoirunisa Khoirunisa; Rudi Tri Handoko; Jemi Cahya Adi Wijaya; Bitsyi Naviri Ismaniar; Beby Dwi Febriyanti (Lembaga Pengembangan Kinerja Dosen, 2025)
This community service activity was carried out as an effort to improve the safety of tourists in the Sendang Seruni water tourism destination, Tamansari Village, Licin District, Banyuwangi Regency. This location is one of the leading tourist attractions with natural panoramas and natural pools sourced from seven mountain springs. However, tourism managers, especially the Sendang Seruni tourism awareness group (Pokdarwis), do not have basic skills in handling emergencies such as water tourism accidents and adequate safety facilities. Based on these conditions, the service team from the Banyuwangi State Polytechnic carried out training and assistance in Basic Life Support (BLS) and First Aid in Accidents (P3K) involving 20 participants from Pokdarwis members. The implementation method includes location surveys, preparation of work plans, theoretical and practical training with professionals from PMI Banyuwangi, and evaluation of the results of activities. Participants were given an understanding of emergency handling such as artificial breathing, cardiac compression, and first aid in water accidents. The results of the activity showed a significant increase in the knowledge and skills of participants related to safety and first aid procedures, as evidenced by competency certification from PMI. In addition, the procurement of safety support facilities such as fire extinguishers, buoys, and P3K boxes also strengthens the preparedness of Pokdarwis in dealing with the risk of accidents in tourist areas. This activity is expected to be a sustainable preventive step in building a culture of tourism safety, as well as supporting the development of sustainable tourism in Banyuwangi.